Performance of Papua Petanque Athletes Facing Covid-19 - Kurdi, Kurdi; Qomarrullah, Rif'iy; Putra, I Putu Eka Wijaya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
This research is a new paradigm mix method by combining grounded theory and case study construction, which involved 11 elite Papuan petanque athletes, data taken from March to May 2020. Data instruments using physical test data, observations, questionnaires, documents, and interviews . Data analysis combines two elements, namely: qualitative, and quantitative. Then the results and discussion in this study are: (1) The health quality of athletes experiencing problems, this is marked by an increase in the proportion of body weight; (2) The physical quality of the athlete experienced a decrease in physical quality before the occurrence of a pandemic above 81.80% and dropped to below 72.70%; (3) Psychologically, when viewed from the aspect of motivation (institutions and extrinsic), it is categorized as high during the pandemic. This research empirically provides a description of the impact received as a result of the Covid-19 outbreak in sports achievements.